'INTEGRATIVE' OR 'INSTRUMENTAL'?: MOTIVATION THAT WORKS CLOSELY DURING THE ADOLESCENCE DAYS OF FEMALE ENGLISH LANGUAGE LEARNERS OF DIFFERENT UNIVERSITIES OF BANGLADESH - Abir, Shazed Ul Hoq Khan (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
From my experience of four years of teaching basic English language skills development courses in two different Universities of Bangladesh, I found that – students with a tendency to be 'integrated with' the culture that comes with the language being taught, have a higher motivation to perform better than other students in classroom communication, as well as in formal exams. In this gender specific case study, focusing on the female students who have done basic English skill development courses with me in two specific universities of Bangladesh, I have attempted to figure out - whether their integrative motivation towards the target language (English) culture is the main driving force to learn English better, or whether is it their instrumental need to learn that particular language that makes them better learners of English. Through personal interviews with my research participants, who showed better competence and obtained better grades than others in my Communicative English class - I tried to figure out their root of motivation to master linguistic competence. In this case study, I have considered Gardner and Lambert's (1972) distinction of integrative and instrumental motivation as my primary source.